Efektivitas Permainan Caterpillar untuk Meningkatkan Hasil Belajar Guling Depan pada Murid Kelas 3 Sekolah Dasar - Dian Wahyuni J; Imam Suyudi; M. Adam Mappaompo; Muh. Adnan Hudain; Muhammadong Muhammadong (Prodi Pendidikan Jasmani dan Olahraga, 2026)
This study aimed to determine the effectiveness of the caterpillar game in improving forward roll learning outcomes among Grade 3 students at UPT SPF SDI Sambung Jawa 3, Makassar City. This research employed a Classroom Action Research (CAR) design with two cycles using the Kemmis and McTaggart model, consisting of planning, acting, observing, and reflecting stages. The research subjects were 28 Grade 3 students comprising 13 male and 15 female students. Assessment instruments covered three domains: cognitive (30%), affective (20%), and psychomotor (50%), with a minimum learning mastery criterion (KKTP) of 80. Results demonstrated significant improvement from the pre-cycle to Cycle II. In the pre-cycle condition, only 3 students (10.7%) achieved the KKTP; this increased to 15 students (53.6%) in Cycle I; and reached 27 students (96.4%) in Cycle II. The caterpillar game proved effective in improving forward roll learning outcomes as the playful approach successfully reduced fear, increased motivation, and developed the fundamental movement coordination required for the forward roll technique.